The graveyard book. volume 2 - Russell, P. Craig; Lafuente, David; Hampton, Scott; Nowlan, Kevin; Showman, Galen; Gaiman, Neil. (London Bloomberry Publishing, 2014)
The concluding volume of the graphic novel adaptation of the book about a boy, raised by the inhabitants of the local graveyard who rally to protect him from a league of villains named Jack that seeks to destroy him.
Keywords: Gaiman, Neil. -- Adaptations; Graphic novels; Dead -- Fiction; Supernatural -- Fiction; Cemeteries -- Fiction; Orphans -- Fiction; Graphic novels